Impact of COVID-19 on Caregiver Burden among Parents of Differently Abled Children: A Survey - Ramya, Chandran; Jagatheesan, Alagesan (INTI International University, 2022)
Introduction: During COVID19 outbreak, parents of differently abled children have to quit their institutional rehabilitation session as a result of pandemic. Many factors lead to depressing experience on caregiver’s mental health, burden, and health status. Caregiver Health Self-Assessment Questionnaire will be helpful in determining the mental behavior and health risk of parents or caregivers of developmentally delayed individuals. Objective: The present study was aimed to examine the impact of COVID19 on caregivers of differently abled children and to compare the burden, stress, and health status of differently abled children’s parents in terms of gender and different age group. Methodology: From the period of October 2020 to March 2021, 30 caregivers of 30 differently abled children’s who were under developmental therapy in child developmental center in Saveetha medical college and hospital were asked to participate in the study through telephonic interview. Results: The mean stress and health status scores among parents of Female children (8 and 7.18) were much higher than parents of male children (5.73 and 4.52). On comparing the age groups, parents of preschool had high caregiver burden and stress mean value of 10 and 7.37, the mean value of school and toddler age group is (8.75, 6.28) and (6.57, 7) parents of infant age group scores lowest burden score compared to the others. Conclusion: Caregivers of differently abled children’s experiences burden, stress and health issues. Children with developmental disability were completely dependent on their caregivers on activities of daily living and decline in their health also inversely have an impact on health status of the caregivers. Our team is working out with home-based exercises facilitated through tele consultation and handouts to reduce the possible impact of COVID19 on these children and caregivers.